Identification of The Alignment between Protected Rice Fields (LSD) and Sustainable Agricultural Land (LP2B) within the Residential Spatial Planning - Johan Irawan; Bambang Hari Wibisono (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Pati, 2025)
INDONESIA Alih fungsi lahan sawah menjadi permukiman di Kabupaten Bantul meningkat akibat tekanan urbanisasi sehingga menimbulkan konflik kebijakan antara Lahan Sawah Dilindungi (LSD), Lahan Pertanian Pangan Berkelanjutan (LP2B), dan Rencana Tata Ruang (RTR). Studi ini menganalisis ketidakselarasan regulasi LSD dan LP2B dengan perencanaan tata ruang perumahan menggunakan analisis spasial berbasis Sistem Informasi Geografis (SIG). Hasil penelitian menunjukkan bahwa terdapat 32 titik potensial konflik antara zona perlindungan pertanian dan peruntukan perumahan, yang diklasifikasikan dalam tujuh tipologi permasalahan. Ketidakselarasan kebijakan ini dapat menyebabkan ketidakpastian hukum, percepatan alih fungsi lahan, dan potensi sengketa tata ruang. Untuk mengatasi permasalahan tersebut, diperlukan sinkronisasi RTR dengan LP2B dan LSD melalui revisi kebijakan, penguatan pengawasan, serta peningkatan koordinasi antara pemerintah pusat dan daerah. ENGLISH The conversion of rice fields into residential areas in Bantul Regency has increased due to urbanization pressure, leading to policy conflicts between Protected Rice Fields (LSD), Sustainable Agricultural Land (LP2B), and the Spatial Plan (RTR). This study analyzes the inconsistencies between LSD and LP2B regulations and residential spatial planning using spatial analysis based on Geographic Information Systems (GIS). The findings indicate 32 potential conflict points between agricultural protection zones and residential allocations, classified into seven problem typologies. These policy misalignment result in legal uncertainty, accelerated land conversion, and potential spatial planning disputes. To address these issues, synchronizing the RTR with LP2B and LSD is necessary through policy revisions, strengthened supervision, and enhanced coordination between central and regional governments.